Efektivitas Penggunaan Media Pembelajaran Audio-Visual Melalui Aplikasi PowerPoint dalam Meningkatkan Hasil Menulis Karangan Deskriptif Bahasa Arab Santri Kelas 6 KMI (Kulliyatul Mu’allimin Al-Islamiyah) : (Di Pondok Modern Tazakka Tahun Ajaran 2025/2026) - Dedi Mulyanto; M. Akhdan Zuhdi (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aimed to examine the effectiveness of audio-visual learning media through PowerPoint in improving Arabic descriptive writing skills among sixth-grade students ITTC at Pondok Modern Tazakka in the 2025/2026 academic year. This research employed a quantitative approach using a pretest–posttest control group experimental design. The sample consisted of 68 students divided into an experimental group and a control group, each comprising 34 students. Data were collected through Arabic descriptive writing tests and analyzed using normality tests, homogeneity tests, the Mann–Whitney test, and N-Gain analysis with SPSS version 27. The results showed that the average posttest score of the experimental group (80.14) was higher than that of the control group (77.79). The Mann–Whitney test yielded an Asymp. Sig. (2-tailed) value of 0.001 (< 0.05), indicating a statistically significant difference between the two groups. Furthermore, the average N-Gain score of the experimental group reached 62.95%, categorized as moderate to high and higher than the control group (56%). These findings indicate that the use of PowerPoint-based audio-visual media is effective in enhancing students’ Arabic descriptive writing skills.